TABDZIR (WASTE) REDUCTION USING LEAN MANUFACTURING APPROACH IN FADHILA AQIQAH TASIKMALAYA PRODUCTION PROCESS - Ahmad Saifullah Mawardi; Lina Marlina; Qiny Shonia Az Zahra (JESKaPe: Jurnal Ekonomi Syariah, Akuntansi dan Perbankan, 2022)
Delay delivery on Fadhila Aqiqah distribution process occurred frequently. The problem was there’re waste in their production process. In islam, it called tabdzir. Tabdzir can minimized so the production process being more efficient. The purpose of this research is to find out how to minimize waste by analyzing the lean manufacturing approach. The research method used is a qualitative approach, namely lean manufacturing with tools in the form of value stream mapping and fishbone diagrams. Value Stream Mapping (VSM) to describe the flow of the production process from raw materials to finished products. VSM is depicted with symbols representing activities, then grouped into value added and non value added. Tabdzir or waste is identified by finding the root of the problem through a fishbone diagram. The implication of this research is that the company is able to know how to minimize the occurrence of waste in the production process.